Characteristic of Harmonic Distortion in Frequency 9-150 Khz Generated by Household Appliances - Yunardi, M. Muaz Afra; Sudiarto, Budi (Syntax Literate, 2021)
The use of household appliances equipped with inverter technology is growing rapidly. As result of using inverters in household appliances, it causes voltage distortion in the electricity network. In induction hobs, the main distortion is in the 20-25 kHz frequency range. Other voltage distortions also exist in the 40-50 kHz frequency range. Since the voltage distortion is seen in the frequency range of integer multiplication of the principal voltage distortion, this can be categorized as a harmonic behavior of the voltage distortion. The second voltage distortion is also known as the 2nd order harmonic distortion. This study aims to determine the behavior of the magnitude of the 2nd order harmonic distortion. To test this phenomenon, measurements using a picoscope with several electronic types of equipment that use inverter technology, such as induction cookers and microwave inverters with various load operating configurations and interconnections between loads against 2nd order harmonic distortion. The results of testing and analysis of the 2nd order harmonic distortion in the load with inverter technology show that the interconnection load affects the magnitude of the 2nd order harmonic distortion. This condition will depend on the characteristic impedance of the distortion source device, neighboring devices, and the main network